Dosimetric feasibility of magnetic resonance (MR)-based dose calculation of prostate radiotherapy using multilevel threshold algorithm - Richard Hugtenburg (Journal of Radiotherapy in Practice, 2017)
Objective: The development of magnetic resonance (MR) imaging systems has been extended for the entire radiotherapy process. However, MR images provide voxel values that are not directly related to electron densities (ED), thus MR images cannot be used directly for dose calculation. The aim of this study is to investigate the feasibility of dose calculations to be performed on MR images and evaluate the necessity of re-planning.Methods: A prostate cancer patient was imaged using both MR and CT. The multilevel threshold algorithm (MLT) was used categorise to voxel values in the MR images in into three segments (air, water and bone) with homogeneous Hounsfield units (HU). An intensity modulated radiation therapy (IMRT) plan was generated from CT images of the patient. The plan was then copied to the segmented MR data sets and the doses were recalculated using pencil beam, and collapsed cone (CC) algorithms and Monte Carlo (MC) modelling.Results: Gamma evaluation showed that the percentage of points in regions of interest with γ < 1 (3%/3 mm) were more than 94% in the segmented MR. Compared with the planning CT (pCT) plan, the segmented MR plan resulted in a dose difference of –0.3%, 0.8% and –1.3% when using PB, CC and MC algorithms, respectively.Conclusion: The segmentation and conversion of MR images into HUs data using the MLT algorithm, used in this feasibility study, can be used for dose calculation. This method can be used as a dosimetric assessment tool and can be easily implemented into the clinic.